An Assessment of Service Quality in Private Higher Education Sector with Respect to Students¶perceptions - Fatima, Shaheen; Ahmad, Aqeel; Fatima, Samreen (International Journal of Psychosocial Rehabilitation, 2024)
Universities are the breeding grounds of societies having intellectuals and knowledge capital. The ratio of private higher education institutions of Pakistanis has been increasing since 2010. The current study attempts to measure determinants of service quality by VWXdenWV¶s perceptions perspective in the most and least influential factors. The population area is private sector HEIs of Pakistan, particularly Lahore. As far as the service quality of private sector HEIs is concerned, this study directs areas for improvements. By following a quantitative approach, data was collected using a questionnaire having five dimensions of service quality and 48 items. Ten private sector HEIs were included in the study as a sample. The Cronbach’s alpha used for this instrument was 0.910 for all the dimensions of service quality. Exploratory factor analysis was used, which extracted nine factors as determinants of service quality of HEIs with VWXdenWV¶ perception perspective. Principal component analysis, the rotated component matrix, elaborates on those eight ineffective items that do not converge in nine factors. Recommendations are provided to improve service quality in those ineffective items of service quality. The study was limited to the private higher education sector of Lahore, and VWXdenWV¶ perception aspect of service quality was considered only. Further researchers can study the government higher education sector by considering various stakeholders perspectives of service quality.